Assessing Nacelle Drag Increment: Implications of New Engine Technologies on Aircraft Performance - Odysseas Ziogas; Spyridon Antoniou; Pericles Panagiotou; Kyros Yakinthos (Engineering Proceedings, 2025)
Τhe Horizon Europe and UKRI-funded MINIMAL project (no. 101056863) aims to develop climate-friendly Composite Cycle Engine (CCE) designs. This study assesses aerodynamic drag increments from new engine installations and their impact on aircraft performance through the development and the utilization of an analytical tool designed to conduct trade studies for estimating the interference drag and drag increment resulting from engine installations. This specialized analytical tool evaluates interference drag due to variations in engine position and size across three reference aircraft (short-range, medium-range, and long-range). Tool results are validated with NASA and ONERA benchmarks, demonstrating good accuracy in predicting aerodynamic impacts. Findings show a 10–15% drag increase from engine installation, offering a reliable approach to optimizing engine integration, ultimately supporting enhanced aircraft efficiency and sustainability.